2y-3=y+3y=6

Simple and best practice solution for 2y-3=y+3y=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2y-3=y+3y=6 equation:



2y-3=y+3y=6
We move all terms to the left:
2y-3-(y+3y)=0
We add all the numbers together, and all the variables
2y-(+4y)-3=0
We get rid of parentheses
2y-4y-3=0
We add all the numbers together, and all the variables
-2y-3=0
We move all terms containing y to the left, all other terms to the right
-2y=3
y=3/-2
y=-1+1/2

See similar equations:

| 4x+2x-6=3x+2 | | -9(3x-11)=6(-4x-5) | | 6.8−4.2b=5.6b–3 | | 7y−3=60 | | k/2-2+7=10 | | -2.4x-9=0 | | −8x−(3x+6)=4–x | | 2-3x-8=72 | | 4y−7+2y=−3(y−1)−1 | | 32p+7=71 | | 180=7x+8=3x-1=4x+5 | | 2/3(3x-1)=7 | | (1/2)x^2-4x-504=0 | | -20-14m=10m+16 | | =2+4y–5 | | 5y-4+y+40=8y+40-4y | | 9(2+w)–4w=3w-10 | | (5x-4)^2=53 | | 10*t=1 | | 30=k+22 | | 10t=1 | | h−3/5=9 | | 14p+15p+21p=9250 | | 17=x-(-18) | | 7.59(4b-10)=46b-b | | 5y-10+y+34=7y+30-4y | | |3x-4|=|x+6| | | 15-3(y-6)=60 | | 24p+25p+14p+19p=820 | | |3x-4|=|x+6 | | -16+4m=-(8-4m) | | |3x-4|=|x+6|; 3)|x^2+3x+2|+|3x+3|=0 |

Equations solver categories